DISCRIMINATION AGAINST JOSEONJOK IN HWANGHAE MOVIE - Fatimazzahroh, Syifa; Latifah, Eva (UI Scholars Hub, 2023)
This research analyzes the discrimination against migrants returning to their homeland. The discrimination occurs because migrants are considered to have no sense of shared fortune and solidarity when the condition of the country was unstable. The government efforts to recall them to return to the country are not often responded well by the local community. They tend to discriminate and reject the existence of migrants who return as brothers. It represents in the movie Hwanghae (2010) by the director Na Hong Jin as a corpus. Thus, this research uses discrimination theory to analyze research problems a ethnic identity theory to analyze the consequences of research problems. This research uses literature review in collecting the data and critical discourse analysis as a method in analyzing the problem. The discrimination against Joseonjok has consequences for the idea of their ethnic identity as part of Korean ethnicity. In general, ethnic identity is correlated with blood relations, but the discrimination experienced by these migrants makes their ethnic identity disguised.